2013
DOI: 10.1007/s00431-013-2191-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of child abuse and associated factors in four secondary institutions in Enugu, Southeast Nigeria

Abstract: Child abuse is a notable problem among secondary school students and adolescents, though this is highly underreported as seen in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
7
11
2
Order By: Relevance
“…This finding is consistent with a study done among high school students in Harar, Eastern Ethiopia; it showed that living with parents had a protective effect on experiencing sexual abuse as compared to living alone [ 16 ]. The finding is also comparable with a study done in South East Nigeria that showed childhood sexual abuse was commoner among students who did not live with their biological parents than those lived with their biological parents [ 14 ]. The possible explanation could be, children who live with their parents are under direct monitoring and follow up that minimize their chance of exposure to opportunistic predators.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with a study done among high school students in Harar, Eastern Ethiopia; it showed that living with parents had a protective effect on experiencing sexual abuse as compared to living alone [ 16 ]. The finding is also comparable with a study done in South East Nigeria that showed childhood sexual abuse was commoner among students who did not live with their biological parents than those lived with their biological parents [ 14 ]. The possible explanation could be, children who live with their parents are under direct monitoring and follow up that minimize their chance of exposure to opportunistic predators.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is much lower than a study conducted among teenagers in South West Nigeria, which was 42.1 % [ 14 ]. This discrepancy may be due to social and cultural variation between the study subjects in reporting CSA; the chance of engaging in marriage is considered as minimal for the female rape survivor in Ethiopia.…”
Section: Discussioncontrasting
confidence: 70%
“…Among the students who experienced violence, 12.9%, 7.9%, 46.5% encountered mild sexual violence (rape), severe sexual violence (rape) and mild physical violence respectively. This nding is lower than studies conducted in other African countries; the life time prevalence of sexual violence (rape) in South West Nigeria and Urban Zimbabwe was 42.1% and 33% respectively (12,13) . This discrepancy might be due to social and cultural variation between the study subjects in reporting sexual violence or rape.…”
Section: Discussioncontrasting
confidence: 57%
“…The aetiology of adult sexual offenses against the underage refers to the origins and causes of sexually abusive behaviour towards minors, which include the pathways that are connected with behavioural development from the onset as well as maintenance. Though, for several years, questions have been asked about the causes of sexual offending (Aderinto, 2010;Banwari, 2011;Chinawa, Aronu, Chukwu, & Obu, 2013;Freund & Kuban, 2014;Garland & Dougher, 2014), they remain relevant today, primarily due to fact that definitive answers have been exceptionally hard to come by and new dimensions of sexual offending which involves the underage in recent times is equally begging for answers (Howitt, 2015;Graham, 2016;Aborisade & Shontan, 2017). While research has facilitated relevant insights about the aetiology of child sexual offending in Nigeria (Aborisade & Fayemi, 2015;Manyike, Chinawa, Aniwada, Odutola, & Chinawa, 2015), our understanding of the origins and causes of sexually abusive behaviour perpetrated against minors remains rudimentary.…”
Section: Introductionmentioning
confidence: 99%